Comparison of Fatty Acid and Gene Profiles in Skeletal Muscle in Normal and Obese C57BL/6J Mice before and after Blunt Muscle Injury - Werner, Jens-Uwe; Tödter, Klaus; Xu, Pengfei; Lockhart, Lydia; Jähnert, Markus; Gottmann, Pascal; Schürmann, Annette; Scheja, Ludger; Wabitsch, Martin; Knippschild, Uwe (Frontiers in Physiology, 2018)
Injury and obesity are two major health burdens affecting millions of people worldwide. Obesity is recognized as a state of chronic inflammation accompanied by various co-morbidities like T2D or cardiovascular diseases. There is increasing evidence that obesity impairs muscle regeneration, which is mainly due to chronic inflammation and to excessive accumulation of lipids in adipose and non-adipose tissue. To compare fatty acid profiles and changes in gene expression at different time points after muscle injury, we used an established drop tower-based model with a defined force input to damage the extensor iliotibialis anticus on the left hind limb of female C57BL/6J mice of normal weight and obese mice. Although most changes in fatty acid content in muscle tissue are diet related, levels of eicosaenoic (normal weight) and DHG-linolenic acid (obese) in the phospholipid and docosahexaenoic acid (normal weight) in the triglyceride fraction are altered after injury. Furthermore, changes in gene transcription were detected in 3829 genes in muscles of normal weight mice, whereas only 287 genes were altered in muscles of obese mice after trauma. Alterations were found within several pathways, among them notch-signaling, insulin-signaling, sonic hedgehog-signaling, apoptosis related pathways, fat metabolism related cholesterol homeostasis, fatty acid biosynthetic process, fatty acid elongation, and acyl-CoA metabolic process. We could show that genes involved in fat metabolism are affected 3 days after trauma induction mostly in normal weight but not in obese mice. The strongest effects were observed in normal weight mice for Alox5ap, the activating protein for leukotriene synthesis, and Apobec1, an enzyme substantial for LDL synthesis. In summary, we show that obesity changes the fat content of skeletal muscle and generally shows a negative impact upon blunt muscle injury on various cellular processes, among them fatty acid related metabolism, notch-, insulin-, sonic hedgehog-signaling, and apoptosis.